PERSEPSI GURU DALAM PENGGUNAAN MEDIA PEMBELAJARAN ONLINE SELAMA PANDEMI COVID-19 (Deskriftif Kualitatif di Gugus Cempaka Kota Bengkulu) - Lisa Aidawati; Rika Partikasari; Lina Try Astuty Sembiring; A Nita (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The purpose of this research is to describe the teacher’s perception in using online learning media during Covid-19 pandemic at Cempaka cluster Bengkulu city. This research is a descriptive qualitative research which has description to explain a research, the subject of this research is teachers of kindergarten/PAUD in Cempaka cluster Bengkulu city. The result of this research is teacher motivate children and increase the children interest in learning by making interesting video. Teachers also work together with parent and send the learning activity for children through WhatsApp application, a lot of problem during online pandemic such as facilities and ineffective learning process.